The Strongest Man - 3 - Dania, Deji (Literamed Publications Nigeria Limited, 2007)
Having unlocked the mystery through cupboard love,the deed is done. Now shaven and blind, Samson becomes a wreck of the brawny Nazirite. As his hair regenerates,his strength is restored for the final assault.
Keywords: Christianity; Bible Stories; Religion